The cyclicality of official bilateral lending: Which cycle do flows follow? - Leopoldo Avellán; Arturo José Galindo Andrade; Tomás Gómez; Giulia Lotti (Inter-American Development Bank (IDB), 2022)
Using a large panel of official bilateral loan data for 111 borrowing countries and 78 lending countries between 1980 and 2020, this paper shows that international government borrowing from bilateral sources is acyclical with respect to the economic cycle of the borrower, but procyclical with respect to the cycle of the lending country. This holds in the case of loans both from advanced economies and from China, currently the largest supplier of official bilateral lending to the average developing country. We find this form of procyclicality most often among middleincome recipient countries across most regions of the world. We also find that bilateral loans follow economic links captured through bilateral trade, and political ties measured by the alignment of votes in the United Nations. The results are consistent across a battery of robustness tests.
Keywords: E60; F32; F34; 330; Bilateral debt; Cyclicality; Capital flows; International government debt